Critical care ultrasound: A national survey across specialties. Issue 3 (13th November 2017) - Stowell, Jeffrey R.; Kessler, Ross; Lewiss, Resa E.; Barjaktarevic, Igor; Bhattarai, Bikash; Ayutyanont, Napatkamon; Kendall, John L.
Abstract: Purpose: Management of the critically ill patient requires rapid assessment and differentiation. Point‐of‐care ultrasound (POCUS) improves diagnostic accuracy and guides resuscitation. This study sought to describe the use of critical care related POCUS amongst different specialties. Methods: This study was conducted as an online 18‐question survey. Survey questions queried respondent demographics, preferences for POCUS use, and barriers to implementation. Results: 2735 recipients received and viewed the survey with 416 (15.2%) responses. The majority of respondents were pulmonary and critical care medicine (62.5%) and emergency medicine (19.9%) providers. Respondents obtained training through educational courses (26.5%), fellowship (23.9%), residency (21.6%), or self‐guided learning (17.2%). POCUS use was common for diagnostic and procedural guidance. Emergency medicine providers were more likely to utilize POCUS to evaluate undifferentiated hypotension (98.5%, P  < .001), volume status and fluid responsiveness (88.2%, P  = .005), and cardiopulmonary arrest (94.1%, P  < .001) compared to other specialties. Limited training, competency, or credentialing were the most common barriers, in up to 39.4% of respondents. Conclusion: Study respondents utilize POCUS in a variety of clinical applications. However, a disparity in utilization still exists among clinicians who care for critically ill patients. Overcoming barriers, such as a lack of formalized training, competency, or credentialing, may lead to increased utilization.